2019
DOI: 10.5487/tr.2019.35.3.279
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamomum camphora Leaves Alleviate Allergic Skin Inflammatory Responses In Vitro and In Vivo

Abstract: In this study, we investigated the therapeutic potential of Cinnamomum camphora leaves on allergic skin inflammation such as atopic dermatitis. We evaluated the effects of C. camphora leaves on human adult low-calcium high-temperature keratinocytes and atopic dermatitis mice. C. camphora leaves inhibited Macrophage-derived chemokine (an inflammatory chemokine) production in interferon-γ (10 ng/mL) stimulated Human adult low-calcium high-tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…In traditional Chinese medicine, the essential oil from this plant (EO) has been widely used to treat inflammation, rheumatic conditions, and muscular strains [ 2 ]. A growing number of pharmacological researches have shown that C. camphora exhibits a wide range of biological activities such as anti-inflammation, anti-bacteria, antioxidation, anti-fungi, and repellent properties [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. In our previous study [ 12 ], 48 constituents from EO were identified; linalool was the major compound, followed by eucalyptol, isoborneol, α-terpineol, and camphor ( Supplementary Material, Table S1 ).…”
Section: Introductionmentioning
confidence: 99%
“…In traditional Chinese medicine, the essential oil from this plant (EO) has been widely used to treat inflammation, rheumatic conditions, and muscular strains [ 2 ]. A growing number of pharmacological researches have shown that C. camphora exhibits a wide range of biological activities such as anti-inflammation, anti-bacteria, antioxidation, anti-fungi, and repellent properties [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. In our previous study [ 12 ], 48 constituents from EO were identified; linalool was the major compound, followed by eucalyptol, isoborneol, α-terpineol, and camphor ( Supplementary Material, Table S1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several sublines of NC mice including NC/Nga, NC/Jic, and NC/Tnd, have been developed [170]. Upon topical application of β-pinene, atopic-like skin conditions in NC/Tnd mice were ameliorated [171,172]. In the atopic dermatitis mouse model induced by 2,4-dinitrochlorobenzene, as well as in an in vitro experiment with a human adult low-calcium high-temperature keratinocytes, Cinnamomum camphora leaves, whose major component is camphor, alleviated atopic dermatitis symptoms and allergic skin inflammatory responses, such as inhibition of chemokine production as well as Jak/STAT and ERK 1/2 phosphorylation.…”
Section: Atopic Dermatitismentioning
confidence: 99%
“…The C. camphora is not only a high-quality resource of wood but also plays an important role in the utilization of fragrance, medicine, and chemical industry due to its special aromatic and medicinal value [ 1 , 2 , 3 , 4 ]. In addition, some studies indicated that the extract of C. camphora leaf and its bioactive components have antioxidant, anti-inflammatory, antialgal, antimicrobial, and insecticidal activities in vitro, as well as the effects of an anticonvulsant, neuroprotective, and alleviating atopic dermatitis in vivo [ 2 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%